Isolation and Identification of Biosurfactant Producing Bacteria From Workshop Wastewater - Asri Ainul; M. Hasbi; Eko Purwanto (Universitas Riau, 2021)
Automotive workshop activities produce oil ills that may pollute waters around the workshop area. The oil-polluted water may inhabit biosurfactant producing bacteria that are able to degrade the oil. A study aimed to isolate and identify the bacteria has been conducted from July to September 2020. The bacteria samples were sampled from workshop wastewater at Kubang Raya street KM 2,5 Pekanbaru, Riau Province and sampling were conducted three times. The bacteria were isolated using TSB (Tryptone Soy Broth) and TSA (Tryptone Soy Agar) media and were identified by using biochemical methods. Results showed that there were seven types of bacteria, namely Providencia, Proteus, Acinetobacter, Bacillus, Aeromonas, Proteus and Serratia. The Emulsification index of Providencia was 38.8%, Proteus 50%, Acinetobacter 48.8%, Bacillus 52,1%, Aeromonas 47,6%, Proteus 54,7% and Serratia 48,8%. Data obtained from this study showed that all of the identified bacteria are able to produce biosurfactants.